Construcción de una máquina extrusora para plástico. - Shingón Collahuazo, Oscar Adrian (2019)
The present technological proposal has as objective the construction of an extruder machine prototype for plastic analyzing the main variables in the process and temperature control pre-ground plastic waste is used as a raw material for the manufacture of 6 millimeters of diameter circular filaments. The machine is mainly constituted by an Archimedes extruder screw that fits precisely inside a cylinder with enough space to turn; the screw has the capacity to push the material from one end to the other at a specific speed. The polymer material is fed by means of a hopper at one end of the machine and due to the thrust action, it flows and mixes in the cylinder and is obtained at the other end with a pre-established geometric profile. This material falls on a roller system that allows a continuous output of the material. The machine serves as a support too for the WPRC research project, which will allow mixing and formulating plastic compounds with other materials, mainly with wood residues.